The Troika in its own words: responding to the politicisation of the southern European crises. Issue 5 (3rd July 2020) - Moreira Ramalho, Tiago
ABSTRACT: The 'post-functionalist' view that growing politicisation constrains further integration ('constraining dissensus') occupies a prominent place in contemporary European studies. However, in the case of the euro crisis, we observe a rise in contentious politics concomitant with a deepening of EU integration, namely in the areas of economic governance. This paper argues that the intervention of the 'Troika' in the struggles over the framing of the southern European crises is a key to this puzzle. The analysis of over 1200 public declarations produced by the three institutions from 2009 to 2016 shows that the Troika actively 'responded' to processes of heightened politicisation, reproducing the dominant crisis narrative of the southern European periphery and making the case for the adequacy and inevitability of austerity. The Troika's success in framing the euro crisis as a result of domestic failure and moral hazard contributed to the legitimation of further integration of European economic governance.